KANDUNGAN UNSUR NITROGEN DAN KARBON PADA KOMPOS DARI BAHAN BAKU SAMPAH ORGANIK YANG DICACAH DENGAN MESIN PENCACAH - Suryawan, I G. P. A.; Hartawan, I G. A. K. D. D.; Kencanawati, C. I. P. K. (Buletin Udayana Mengabdi; Vol 15 No 1 (2016): Jurnal Udayana Mengabdi, 2016)
Separator of organic waste for raw material of compost have been made in the design of machine elements, with a knife cut several times modifications have been carried out. Linggasana communities close to the waste treatment facility (TPA) Karangasem municipal solid waste has been conducting composting, but the process is still a long decay, this is due small size raw materials and it is not added yet accelerate the decomposition actuators. Denbantas community has similar problems. So many potentials, but still can not properly utilized due to lack of knowledge related to these fields.The purpose devotion Linggasana Buana Giri and Denbantas village is to empower and increase community participation in building regional potential and improve people's welfare in the economy through the development of household waste and agriculture for compost. Composting process lasts for 5-6 weeks, the results in the test in laboratory of Mechanical Engineering and in the laboratory of Soil Science Faculty of Agriculture, University of Udayana. Compost soil with K samples (taken at Linggasana Karangasem) nitrogen content is 0.78 and C / N ratio is 21.7, while the sample T (taken in Denbantas Tabanan) content of nitrogen is 0.19 and C / N ratio is 58, 6. This happens because the materials in Linggasana more compost mixed with manure to provide the nitrogen element needed by plants, and compost quality incoming SNI standard.
Keywords: organic waste, separator, compost.